HUBUNGAN KEPEMIMPINAN KEPALA SEKOLAH DAN TINGKAT PARTISIPASI GURU DALAM PELAKSANAAN MANAJEMEN BERBASIS SEKOLAH - Hidayat, Muhammad Randi; Giatman, M.; Yuliarma, Yuliarma; Mardizal, Jonni (STKIP Pesisir Selatan, 2025)
This study aims to examine the relationship between principal leadership and teacher participation in the implementation of School-Based Management (SBM) at SMK Negeri 7 Sijunjung. The background of this research lies in the crucial role of school leadership in fostering a participatory, transparent, and accountable organizational climate, which is essential for the effective implementation of SBM and the improvement of educational service quality. This study employed a quantitative approach with a correlational research design. The population consisted of 32 permanent teachers at SMK Negeri 7 Sijunjung, while the principal was involved as a key informant to strengthen the contextual understanding of field data. Data were collected through questionnaires and analyzed using descriptive and inferential statistical techniques, specifically the Pearson Product Moment correlation test. The findings reveal that the principal’s leadership is in the very good category, with an average score of 4.21, while teacher participation is categorized as high, with an average score of 4.08. The correlation test results indicate a positive and significant relationship between principal leadership and teacher participation, with a coefficient of r = 0.742 (p < 0.05). These results confirm that the more effective the principal’s leadership, the higher the level of teacher participation in SBM implementation, which ultimately contributes to the improvement of educational service quality at the school.